Study of the relationship between the rutting values and the properties of materials for flexible pavement using computer modeling - اللهيبي, محاسن; رامي حنا, (Latakia University Journal -Engineering Sciences Series, 2023)
The problems associated with the cracking of flexible pavement are among the issues for which solutions have been incomplete for decades, due to the difficulty of linking the properties of the materials formed for the pavement and the thicknesses of the pavement, as well as the mutual relationship between the various layers that form them, especially using traditional relationships and methods. However, during the past decades, mathematical methods have been successfully used, the most important of which is the finite element method, in the careful analysis of various pavement problems. In this study, the pavement layers were modeled and analyzed using two-dimensional analysis (the use of specific two-dimensional elements) using the Abaqus program in order to verify the effect of repeated wheel load on the occurrence of rutting through the response and interaction of the pavement layers with it and with time. Our model is real pavement layers with different material properties and subject to different loads using finite element theories in order to properly predict the rutting values and their location, where the behavior of unbound materials was considered (linear elastic behavior) based on the (Drucker Prager) model, as for the behavior of the asphalt layer it was modeled as a visco plastic behavior. We considered the design load as the tire inflation pressure (0.7 MPa) with a cyclic load of 100,000 load cycles within a time of 100 seconds. The expected rutting depth through the Abaqus program was compared with the rutting depth calculated from traditional relations, and the results showed that the rutting depth using the visco plasticity model of the asphalt layer matches the rutting depth calculated by 86% for the Jableh Highways model, and 95% for the northern Highways model of Lattakia city, in addition to It is indicated that the time periods for the occurrence of rutting exceed the design life of the pavement (15 years).